- #1

- 34

- 0

Well, when we do Integration by parts we will have [tex]let[/tex] [tex] u = x [/tex] [tex] du = dx [/tex] [tex]dv = e^{-x}dx[/tex] [tex]v = -e^{-x}[/tex] so that would give us [tex]\int_{0}^{\infty}x e^{-x}dx= - x e^{-x} + \int_{0}^{\infty} e^{-x}dx [/tex] evaluating the second term will just yield 1, so, [tex]\int_{0}^{\infty}x e^{-x}dx= - x e^{-x} + 1,[/tex] the second term should yield zero by employing limits as x approaches infinity, [tex] \lim_{x\rightarrow \infty }xe^{-x}=0 [/tex] but whoa, it didn't. I will yield instead [tex]1/e[/tex] Where did I went wrong?